Measurement of human body aura using resonant field imaging / Zunairah Murat, Mohd Nasir Taib and Nooraini Hana Mokhtar - Murat, Zunairah; Taib, Mohd Nasir; Mokhtar, Nooraini Hana (2004)
This paper presents the measurements and analysis of human body aura using the Resonant Field Imaging (RFI) system. The understanding of bioenergy and its relationship with the human body were obtained from the frequency measurement at 36 points on the human body. Using custom designed software, the RFI measurements were then interpreted to show the psychology and physiological states of the human sample.